The Premarital Drug Testing in Binjai Mayor Regulation Number 39 of 2017 in Terms of Maqāṣid Asy-Syarī’ah - M. Prayudha Aprian (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The current phenomenon, many Indonesian people, especially in the city of Binjai, ended their household ark with divorce, one of which was drug. Then premarital drug testing in Binjai mayor regulation number 39 of 2017 as a requirement to get a control card / NA. Every rule / policy issued certainly has a purpose. Then Islam has rules (Shari'at) which aim to produce benefits and reject mafsadat. As for the benefits of drug testing is to maintain religion, self, reason, descent and wealth. This study aims to determine maqāṣid asy-syarī'ah against premarital drug testing in Binjai mayor regulation number 39 of 2017. Then the result is maqāṣid asy-syarī'ah against pre-marital drug testing in Binjai mayor regulation number 39 of 2017. Then the result is an existence in terms of maqāṣid asy-syarī'ah towards pre-marital drug testing in Binjai mayor regulation number 39 year 2017. Then the result of maqāṣid asy-syarī'ah towards pre-marital drug testing in Binjai mayor regulation number 39 year 2017. 2017 is showing the benefit of preserving religion, self, reason, descent and wealth.